Media Silence on Suicide in Nigeria's News Coverage - Okunade, Joshua Kayode; Amaechi, Deborah Onyinyechi; Olopha, Anthony; Aondover, Eric Msughter (Feedback International Journal of Communication, 2025)
Suicide is a pressing public health concern in Nigeria, yet the extent to which it is reported in the media remains unclear. The mass media serves a critical role in shaping public awareness and framing social issues. This study explores how suicide cases are reported by Nigerian online newspapers and whether such coverage aligns with the media’s social responsibility. Using a quantitative content analysis method, the study examined suicide-related articles published in The Punch and The Guardian online editions between April and December 2019. A total of 540 newspaper issues (270 from each outlet) were analyzed using purposive sampling. Data were categorized based on story frequency, genre, paragraph length, and number of deaths reported. Theoretical framing was guided by Agenda-Setting Theory, Cultivation Theory, and Social Responsibility Theory. A total of 75 suicide-related stories were identified. Most were brief (1–10 paragraphs) and appeared in the metro section, with little investigative or thematic depth. The Punch contributed more stories (57.3%) compared to The Guardian (42.7%). Despite the high number of suicides in Nigeria, the overall media coverage was found to be minimal and inconsistent. Findings suggest significant underreporting and a lack of meaningful engagement with suicide as a societal issue. The media has not fulfilled its role in setting the public agenda or cultivating awareness. Suicide is often framed episodically rather than thematically, limiting its visibility as a public health concern. This undermines the media’s potential to educate, warn, and mobilize action against suicide. The study concludes that Nigerian newspapers have not adequately reported on suicide, failing to meet the standards of socially responsible journalism. Broader media monitoring and audience-focused research are needed to understand the full impact of media coverage on suicide perception and prevention.